Addition of hydrogen peroxide enhances abiotic sunlight-induced processes to simultaneous emerging pollutants and bacteria abatement in simulated groundwater using CPC solar reactors. (15th May 2017) - Gutiérrez-Zapata, Hector Mario; Sanabria, Janeth; Rengifo-Herrera, Julián Andrés
Highlights: 2, 4-D was removed by the addition of 10 mg L −1 of H2 O2 and sunlight irradiation. E. coli viability was completely reduced by the addition of H2 O2 and sunlight irradiation. K. pneumoniae showed high resistance and its viability was partially reduced. Different photo-induced processes are responsible of 2, 4-D and E. coli removal. Graphical abstract: Abstract: Results revealed that almost 90% of 2, 4-D (70 μg L −1 ), present in simulated groundwater containing 0.3 mg L −1 of iron at pH 7.0, was degraded after 320 min (60 min t30w ) of natural sunlight irradiation while the viability of Escherichia coli cells (followed by DVC-FISH) was completely reduced after 220 min (40 min t30w ) by simple addition of 10 mg L −1 of hydrogen peroxide. Klebsiella pneumoniae exhibited an especial behavior since its viability was only reduced in 3.5 logs after 320 min of sunlight irradiation (60 min t30w ). Dark experiment (in presence 10 mg L −1 of H2 O2 ) showed that Fenton processes may also play an important role reducing the 40% of 2, 4-D after 320 min (60 min t30w ) while viability of E. coli and K. pneumoniae underwent a reduction of 2.5 and 2 logs respectively. Photolysis experiments were not able to degrade 2, 4-D and E. coli and K. pneumoniae viability was partially reduced (2 logs). Results showed that high 2, 4-D abatement could be due to photo-induced and/or dark processes such as photo-Fenton and Fenton (dissolved and colloidal iron), photocatalysis (colloidal iron) and UV-B photolysis of H2 O2 . Viability reduction of microorganisms should be related to combined effects of UV-A + B irradiation, rising of temperature (44 °C), photo-Fenton, Fenton and photocatalytic processes.